VD_FINDINFO Jug / 2011 / 97 vom 2. Februar 2011 - VD Tribunal cantonal (2011)
TRAVAIL D'INTÉRÊT GÉNÉRAL, RÉVOCATION DU SURSIS, ESCROQUERIE, ABUS DE CONFIANCE, FIXATION DE LA PEINE | 146 al. 1 CP, 37 al. 1 CP, 46 al. 2 CP, 47 CP